2005
DOI: 10.1128/jb.187.23.7996-8005.2005
|View full text |Cite
|
Sign up to set email alerts
|

Growth Substrate- and Phase-Specific Expression of Biphenyl, Benzoate, and C 1 Metabolic Pathways in Burkholderia xenovorans LB400

Abstract: Recent microarray experiments suggested that Burkholderia xenovorans LB400, a potent polychlorinated biphenyl (PCB)-degrading bacterium, utilizes up to three apparently redundant benzoate pathways and a C 1 metabolic pathway during biphenyl and benzoate metabolism. To better characterize the roles of these pathways, we performed quantitative proteome profiling of cells grown on succinate, benzoate, or biphenyl and harvested during either mid-logarithmic growth or the transition between the logarithmic and stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 45 publications
3
84
0
Order By: Relevance
“…No growth of LB400 on C 1 compounds has yet been reported; however, growth was observed on the methylated-glycine derivatives betaine and choline (23). Because many plant aromatic compounds are methylated or methoxylated, it is possible that these C 1 pathways are involved in plant aromatics metabolism, which is a possible explanation for their coexpression in biphenyl-grown LB400 cells at transition to stationary phase (33,44).…”
Section: Genetic Factors Indicating the Ecological Niche Of B Xenovomentioning
confidence: 92%
See 2 more Smart Citations
“…No growth of LB400 on C 1 compounds has yet been reported; however, growth was observed on the methylated-glycine derivatives betaine and choline (23). Because many plant aromatic compounds are methylated or methoxylated, it is possible that these C 1 pathways are involved in plant aromatics metabolism, which is a possible explanation for their coexpression in biphenyl-grown LB400 cells at transition to stationary phase (33,44).…”
Section: Genetic Factors Indicating the Ecological Niche Of B Xenovomentioning
confidence: 92%
“…Redundancy is not entirely unexpected because these organisms presumably have to contend with varying conditions in nutrient source types and concentrations. The latter is exemplified by the detailed study of benzoate catabolism, which suggests that each of these pathways is conditionally regulated depending on benzoate and oxygen levels presented to the cell (33). Further studies of LB400 metabolic and other functional redundancies, such as the presence of multiple Type IV secretion systems (see Burkholderia virulence-associated genes), will be important to gain a better understanding of their evolutionary origin, their role, and whether or not there is a selective benefit of functional redundancy in large-genome bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several bacterial strains contain both the classical and the hybrid pathway for aerobic benzoate degradation. The box pathway was suggested to be specially active at reduced oxygen tension (20,23,24). An in silico search among the available bacterial genomes revealed that most box clusters are organized into at least two major functional catabolic units; 1) the activation module (encoded by the bclA gene) and 2) the dearomatization and ring-cleavage module encoded by the boxAB and boxC genes, respectively.…”
mentioning
confidence: 99%
“…The pathways for degradation of PCBs by strain LB400 have been extensively characterized at both the genetic and the molecular level [30,31] and the complete sequencing of the LB400 genome (http://genome.ornl.gov/microbial/bfun) [32], one of the largest ones among prokaryotes (9.7 Mb), greatly contributed to the investigation of the biology of PCB degradation. By use of genomic and proteomic approaches, an outline of genome-wide responses to a range of carbon and cell development conditions has been reported [33,34]. Putative detoxification mechanisms were also revealed during analysis of the transcriptome of B. xenovorans LB400 [35] and recent studies, aimed at exploring the effect of environmental conditions (e.g., carbon source and growth phase) on the variation in PCB degradation profiles of Burkholderia xenovorans LB400, revealed 25 potential genes involved in the activation of mechanisms beyond the biphenyl pathway that provide stability and improve PCB degradation [36].…”
Section: Com)mentioning
confidence: 99%